Correlation between seasonal and meteorological factors with the monthly frequency of intracranial aneurysms rupture in northeast Mexico - Alcalá Briones, Ricardo Daniel; Villarreal Silva, Eliud Enrique; Flores Benavides, Lydia Itzel; Ramos Delgado, César; Martínez Bustamante, Daniel; Martínez Ponce de León, Ángel Raymundo (Elsevier, 2021)
Intracranial aneurysms are considered acquired lesions, occur with an incidence of 3–5% in general population. Subarachnoid hemorrhage (SAH) due to ruptured aneurysms represents 85 of all spontaneous subarachnoid hemorrhages and this represents 15% of all cerebral vascular events. Risk factors for aneurysmal rupture are age, gender, size and location of the aneurysm, hypertension, smoking, and alcoholism. Whether seasonal or meteorological factors influence the likelihood of aneurysm rupture is controversial. An observational, retrospective, cross-sectional and non-comparative study of male and female patients over 18 years old who were admitted to our unit in northeast Mexico with the diagnosis of spontaneous SAH due to aneurysmal rupture from January 2014 to March 2020. Climate information was obtained from data of the climate history of the different airport stations in the northeast of the country and the information was correlated to determine if meteorological variables interfere in the incidence of SAH due to aneurysm rupture. Our study showed a significant seasonal fluctuation on the occurrence of aneurysmal SAH. A statistically significant relationship between temperature, humidity and aneurismal SAH. The atmospheric pressure did not show a statistically significant relationship with SAH incidence due to aneurysm rupture.